Question
upstudy study bank question image url

Solve. \( 3 y-1-9 y=29 \)

Ask by Chadwick Pope. in Brazil
Feb 26,2025

Upstudy AI Solution

Tutor-Verified Answer

Answer

A solução da equação é y = -5.

Solution

Vamos resolver a equação: 3y - 1 - 9y = 29 1. Primeiro, combine os termos semelhantes: 3y - 9y = -6y. Assim, a equação fica: -6y - 1 = 29 2. Em seguida, isole o termo que contém y adicionando 1 dos dois lados: -6y = 29 + 1 -6y = 30 3. Por fim, divida os dois lados por -6 para encontrar y: y = 30 / (-6) y = -5 Portanto, a solução da equação é y = -5.

Answered by UpStudy AI and reviewed by a Professional Tutor

error msg
Explain
Simplify this solution

Mind Expander

To solve the equation \( 3y - 1 - 9y = 29 \), first, combine like terms. This results in: \[ 3y - 9y - 1 = 29 \] which simplifies to: \[ -6y - 1 = 29 \] Next, add 1 to both sides: \[ -6y = 30 \] Now, divide by -6: \[ y = -5 \] So the solution is \( y = -5 \). If you want to double-check your solution, simply plug \( y = -5 \) back into the original equation to see if both sides are equal. This practice will help ensure you're on the right track! Solving linear equations can be a piece of cake with the right approach! Just remember to simplify step-by-step, and keep an eye out for those pesky signs – they can easily throw off your result if you're not careful!

Try Premium now!
Try Premium and ask Thoth AI unlimited math questions now!
Maybe later Go Premium
Study can be a real struggle
Why not UpStudy it?
Select your plan below
Premium

You can enjoy

Start now
  • Step-by-step explanations
  • 24/7 expert live tutors
  • Unlimited number of questions
  • No interruptions
  • Full access to Answer and Solution
  • Full Access to PDF Chat, UpStudy Chat, Browsing Chat
Basic

Totally free but limited

  • Limited Solution
Welcome to UpStudy!
Please sign in to continue the Thoth AI Chat journey
Continue with Email
Or continue with
By clicking “Sign in”, you agree to our Terms of Use & Privacy Policy